Error sources for the analysis of doppler broadening in positron annihilation spectra - Otero, Dino; Proto de Otero, A. N.; Romero, R.; Somoza, A. (Springer-Verlag, 1982)
Fil: Otero, Dino Comisión Nacional de Energía Atómica; Argentina